Factors Influencing Rice Procurement at Bulog Office Central Kalimantan Region - Sitorus, Sefti Yafia Boru; A.D, Yuprin; Pordamantra, Pordamantra (Central Research Institute For Agriculture, 2023)
Procurement of staple materials by Perum Bulog, especially rice, has quality standards that must be applied to all rice, so there is a need for rice supervision to determine the feasibility of the rice given to consumers. The purpose of this research is to find out the monitoring process carried out by Perum Bulog in order to get the quality of rice according to the quality standards set. The results showed that the quality of Bulog's rice procurement was in accordance with the quality of rice determined by BULOG itself. The results of this overall inspection concluded that the Central Kalimantan Regional Office of the Bulog Regional Office conducted the procurement and supply of rice according to the applicable quality standards and the rice that was distributed was suitable for consumers.